Impact of biodiesel demand on the Malaysian palm oil industry: A simultaneous equations approach - Applanaidu, Shri Dewi; Mohamed Arshad, Fatimah; Shamsudin, Mad Nasir; Alias, Mohammad (Universiti Utara Malaysia Press, 2011)
The European Union (EU) Renewable Energy Directive set a target of 20 % share of energy from the renewable sources and 10% share of renewable energy specifically in the transport sector.This has resulted in some countries looking for bio-based alternative energies which lead to the increase in demand for bio-based feedstocks such as palm and rapeseed oil (for biodiesel) and sugar cane and corn (for ethanol).One of the new elements in the palm oil market is the growing demand for this commodity as a feedstock to biodiesel production.This will also put Malaysia in a better light on the international front for taking the effort to reduce carbon emissions.In line with this, the palm oil sector in Malaysia will be able to match the New Economic Model’s (NEM) major goals of high income, sustainability and inclusiveness.This new development is affecting the dynamics of the market, in particular, the supply and demand sectors of this commodity.This paper seeks to examine the impact of biodiesel demand on the Malaysian palm oil industry.This paper proposes a structural econometric model consisting of nine structural equations and four identities.The model has been estimated by the two stage least squares method using annual data for the period 1976–2010.The specification of the structural model is based on a series of assumptions about general economic conditions, agricultural policies and technological change.The study indicates that counterfactual simulation of a sustained 30% increase in biodiesel demand predicts a positive increase (2.48%) in palm oil exports for non-biodiesel, 13% increase in the domestic price of palm oil and a marginal increase in production.An increase in export demand would make Malaysia more competitive regionally and globally with benefits accruing to all Malaysians.Apart from this, the biodiesel demand income is also sustainable and will position the nation on the right path towards a high income country by 2020